Surveying perceptions and practices of high-end climate change - Taylor, Richard (2020)
We surveyed members of the adaptation community about their views on high-end climate change—here defined as global average temperature increase exceeding 2 °C at the end of the century—at consecutive conferences in 2016 and 2018. Most strikingly our surveys show that a majority of the community disagrees that the Paris Agreement has reduced the possibility of the world reaching dangerous levels of climate change. Consistent with this, around two thirds of people consulted are considering high-end climate change or using high-end scenarios in their work all the time, or starting to. However, this is still not done by all. Preparedness for the specific threats posed by high-end impacts is not keeping pace, and more work needs to be done to strengthen the research basis and understand adaptation needs under high-end climate change. Moreover, views on finding information on impacts and tools for decision-making have not changed between 2016 and 2018, showing that there is no improvement. This situation underlines that the adaptation community needs to do better in supporting exchange of information and data between all actors—in addition to finding and filling knowledge gaps. Despite this, there is widespread support for avoiding delaying large-scale adaptation until we have more certainty.